Impact of Adolescent Intermittent Ethanol Exposure on Social Investigation, Social Preference, and Neuronal Activation in cFos-LacZ Male and Female Rats - Towner, Trevor T.; Applegate, Devon T.; Varlinskaya, Elena I.; Werner, David F. (Frontiers in Pharmacology, 2022)
Adolescence is a sensitive developmental period during which alcohol use is often initiated and consumed in high quantities, often at binge or even high-intensity drinking levels. Our lab has repeatedly found that adolescent intermittent ethanol (AIE) exposure in rats results in long-lasting social impairments, specifically in males, however our knowledge of the neuronal underpinnings to this sex-specific effect of AIE is limited. The present study was designed to test whether social anxiety-like alterations in AIE-exposed males would be accompanied by alterations of neuronal activation across brain regions associated with social behavior, with AIE females demonstrating no social impairments and alterations in neuronal activation. Adolescent male and female cFos-LacZ transgenic rats on a Sprague-Dawley background were exposed to ethanol (4 g/kg, 25% v/v) or water via intragastric gavage every other day during postnatal days (P) 25 – 45 for a total of 11 exposures (n = 13 per group). Social behavior of adult rats was assessed on P70 using a modified social interaction test, and neuronal activation in brain regions implicated in social responding was assessed via β-galactosidase (-gal) expression. We found that AIE exposure in males resulted in a significantly lower social preference coefficient relative to water-exposed controls, with no effect evident in females. Exposure-specific relationships between social behavior and neuronal activation were identified, with AIE eliminating correlations found in water controls related to social interaction, and eliciting negative correlations mainly in limbic regions in a sex-specific manner. AIE exposure in the absence of social testing was also found to differentially affect neural activity in the orbitofrontal cortex and central amygdala in males and females. These data suggest that AIE produces sex-specific social impairments that are potentially driven by differential neuronal activation states in regions important for social behavior, including the medial prefrontal and orbitofrontal cortices, nucleus accumbens, lateral septum, and central amygdala. Future studies should be focused on identification of specific neuronal phenotypes activated by interaction with a social partner in AIE-exposed subjects and their control counterparts.